Gender roles: hegemony and aesthetics in children's advertisements in in the advertisements for boys and girls in Chanchito - Peters-Rada, Victoria Eugenia; González-Buitrago, Lucy Johana (Mundo FESC Journal, 2022)
Gender roles, understood as social constructs, prototypes of the “should be” that are taught and reinfor-ced from childhood, are part of those notions that have been addressed by advertising since the 1930s, to establish those behaviors and habits expected in a man or a woman, a distinction that is also evident in advertising aimed at infants. Advertising has been, undoubtedly, one of the branches of communi-cation through which various ideas have been extended to society, with the interest of encouraging the adoption of certain beliefs or behaviors, generally promoted from some positions of power. This article aims to show how these hegemonic discourses in relation to gender roles were present in advertising aimed at children, readers of the children’s magazine Chanchito, which circulated in Colombia be-tween 1933 and 1934. Through a case study, with a qualitative approach, we seek to characterize the 1323 advertisements of the magazine in relation to the themes, the language, and the graphic propo-sal presented in each of these pieces; characterization that reflects the latent concern of the time on how to direct children towards the gender roles associated with the idea of being a man or a woman.